Hohe Feste, niedere Feste. Der liturgische Festalltag in den Konventen des Deutschen Ordens - Löffler, Anette (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2024)
High feasts, low feasts. The everyday liturgical festivities in the convents of the Teutonic Order The liturgical life of the priest brothers of the Teutonic Order took place to a considerable extent in the convents and castles. Depending on the degree of celebration, the daily festivities in the Teutonic Order were organized. Complex liturgical regulations regarding the prioritization of the feasts had to be followed, which resulted from the degree of the feast. The higher the degree of celebration, the more extensive and complex the liturgy was on this and other days. The existing festival calendar also had to be taken into account, in which men's feasts, Sundays, movable feasts and saints’ feasts had to be classified. However, the definition of a feast by its degree of celebration was already recorded differently in the underlying liturgical manuscripts. The forms in the liturgical manuscripts, in turn, sometimes differed from the entries in the calendars. Even with a requirement in the standards code, the range was wide. The example of the fixed degree commemoratio shows very clearly what deviations can occur. Over time, the liturgy of the Teutonic Order changed, so that new festivals were added and the degree of celebration of existing festivals was changed. This is also shown by the feast of St. Barbara of Nicomedia, in which, despite all the uniformity, individual characteristics came into play. This means an elevation from the lowest level of celebration, the commemoratio, to a solemnity with its own rhyme office.